Somatic Embryogenesis in Musa Spp. - Kabir, Md. Humayun (2002)
Embryogenesis competent material (scalp) was initiated from shoot tip of Musa spp. cultivar Mas (AA), Berangan (AAA), Intan (AAA), Raja (AAB) and Tanduk (AAB). Somatic embryogenesis were investigated from four explant sources viz., scalps, male flower primordia, in vitro corm slices and immature ovules of Musa acuminata cv. Mas. Scalp formation was optimal on Murashige and Skoog (MS) medium with modified vitamins supplemented with 100 /lM BAP and 1.0 /lM IAA. Among the cultivars investigated, cv. Mas was the most responsive for scalp formation whereby 40% of the shoot tips formed scalps by the 7th month of culture. Cultivar Mas was also the most responsive for meristematic globule formation from scalps attaining 100% meristematic globule formation by week 7 of culture of scalps in Z medium. Cells with embryogenic potential were released from the meristematic globules of cv . Mas after 10 to 12 months of culture of the meristematic globules in Z medium . The embryogenic cell suspension was transferred to liquid S medium and formed globular embryos after 3 to 4 months in culture. Matured globular embryos upon transfer to liquid S regeneration medium supplemented with 0, 1.0, 5.0, 10, 20, 40 and 80 /lM BAP germinated to form roots but without shoots.